2018
DOI: 10.1029/2018je005719
|View full text |Cite
|
Sign up to set email alerts
|

Geological Features and Evolution of Yardangs in the Qaidam Basin, Tibetan Plateau (NW China): A Terrestrial Analogue for Mars

Abstract: Wind‐eroded ridges known as yardangs are common in most arid desert regions on Earth, as well as on other planets, notably in the Medusae Fossae Formation (MFF) and Gale Crater on Mars. However, the formation and evolution of these various yardangs are not well understood, which, therefore, requires further studies by more terrestrial analogues. Here we report a detailed investigation of the terrestrial yardang fields in the Qaidam Basin, northeastern Tibetan Plateau, China. Most of them are distributed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 96 publications
1
31
0
Order By: Relevance
“…Line 4 may represent the largest visible extent of the yardang. We have measured the lengths and widths of the different period yardang parts, and find their aspect ratios to be 2.9:1, 3.2:1, 2.8:1, and 3.3:1 for the lines 1, 2, 3, and 4, respectively, which are consistent with previous data for whaleback yardangs under wind erosion (Li JY et al, ; Hu CQ, ; Wang J et al, ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Line 4 may represent the largest visible extent of the yardang. We have measured the lengths and widths of the different period yardang parts, and find their aspect ratios to be 2.9:1, 3.2:1, 2.8:1, and 3.3:1 for the lines 1, 2, 3, and 4, respectively, which are consistent with previous data for whaleback yardangs under wind erosion (Li JY et al, ; Hu CQ, ; Wang J et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Data sets of this sort have great potention to shed light onto past local wind characteristics. Comparative planetary study. Previous studies have shown that the yardangs in Qaidam Basin are closely analogous to yardangs on Mars (Xiao L et al, ; Anglés and Li YL, ; Wang J et al, ). However, the relatively low resolution of the terrestrial satellite data could not support a comprehensive comparative study of the yardangs on both planets.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The modern yardangs formed nearly simultaneously since~105 ka (section 6.1) and are up to 20-30 m high (Wang et al, 2018) in the QB, corresponding to a wind erosion rate of~0.19-0.29 mm/a. However, the pattern of faster wind erosion in the last glacial period than the present-day interglacial period can be expected for the entire QB.…”
Section: Wind Erosion Rate and Its Secular Variationmentioning
confidence: 99%